2013
DOI: 10.1186/1471-2377-13-47
|View full text |Cite
|
Sign up to set email alerts
|

Impaired small fiber conduction in patients with Fabry disease: a neurophysiological case–control study

Abstract: BackgroundFabry disease is an inborn lysosomal storage disorder which is associated with small fiber neuropathy. We set out to investigate small fiber conduction in Fabry patients using pain-related evoked potentials (PREP).MethodsIn this case–control study we prospectively studied 76 consecutive Fabry patients for electrical small fiber conduction in correlation with small fiber function and morphology. Data were compared with healthy controls using non-parametric statistical tests. All patients underwent neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 36 publications
5
56
0
2
Order By: Relevance
“…However, with the finding that abnormalities were also found in the patients without FD (specificity 80%), it is safe to draw the conclusion that small nerve fibre assessment is most likely an unsuitable tool for establishing the diagnosis of FD in patients who present with an uncertain diagnosis. In previous studies, it has been shown that all male and most female patients with (mostly classical) FD have small nerve fibre pathology, as assessed with QST alone or in combination with an IENFD assessment (Dutsch et al 2002;Laaksonen et al 2008;Biegstraaten et al 2011Biegstraaten et al , 2012€ Uçeyler et al 2011€ Uçeyler et al , 2013. With this study, we confirmed our hypothesis that in patients with the nonclassical phenotype QST and/or IENFD may be abnormal, even in the absence of pain.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, with the finding that abnormalities were also found in the patients without FD (specificity 80%), it is safe to draw the conclusion that small nerve fibre assessment is most likely an unsuitable tool for establishing the diagnosis of FD in patients who present with an uncertain diagnosis. In previous studies, it has been shown that all male and most female patients with (mostly classical) FD have small nerve fibre pathology, as assessed with QST alone or in combination with an IENFD assessment (Dutsch et al 2002;Laaksonen et al 2008;Biegstraaten et al 2011Biegstraaten et al , 2012€ Uçeyler et al 2011€ Uçeyler et al , 2013. With this study, we confirmed our hypothesis that in patients with the nonclassical phenotype QST and/or IENFD may be abnormal, even in the absence of pain.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have shown that all male and most female patients with (classical) FD have an abnormal quantitative sensory testing (QST) profile and a decreased intraepidermal nerve fibre density (IENFD) in a skin biopsy at the distal leg (Dutsch et al 2002;Laaksonen et al 2008;Biegstraaten et al 2011Biegstraaten et al , 2012€ Uçeyler et al 2011€ Uçeyler et al , 2013. We hypothesized that QST and IENFD could aid in the diagnosis of FD in patients who initially present with an uncertain diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of cold perception is thought to be an important somatosensory entity, which may be altered in the early stage of small‐fibre neuropathy (such as in Fabry's disease; (Maag et al, ; Uceyler et al, )). Previous studies reported cold sensation loss in 40% of polyneuropathy, 63% of postherpetic neuralgia, 50% of peripheral nerve injury and 49% of central pain patients (Maier et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of pain in Fabry disease is not fully understood; however, SFN as a result of glycolipid accumulation in the dorsal root ganglia has been proposed [39] and confirmed [40] as a mechanism. Indeed, small fibre conduction is impaired in men with Fabry disease and worsens with advanced disease severity [41]. Indeed, 100% of male patients and 57% of female patients have a decrease of IENF density [40].…”
Section: Fabry Diseasementioning
confidence: 99%